PENERAPAN SANKSI ADMINISTRATIF TERHADAP PELANGGARAN PENATAAN RUANG KOTA MEDAN - AIDO FITRA LAMENDES (PREMISE LAW JURNAL, 2018)
DOESN PEMBIMBING:1. Saidin2. T. Keizerina Devi A3. Faisal Akbar Nasution A city is a place where people’s social economic activities are concentrated with a very dynamic development. In order to optimize the city development, the municipal land-use plan needs to be directed in the municipal spatial plan consisting of spatial structure and pattern. Article 11 paragraph (2) of the Law No. 26/2007 on Spatial Plan states that a municipality has the authority to the implementation of its spatial plan, including the municipal spatial plan, land-use plan and land-use control. This authority is granted to all municipalities in Indonesia, including Medan.Keywords: Spatial Plan, Administrative Sanction, Medan Municipality